2012
DOI: 10.1007/s10029-012-0901-x
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of randomized controlled trials comparing lightweight and heavyweight mesh for Lichtenstein inguinal hernia repair

Abstract: The use of lightweight mesh in Lichtenstein inguinal hernia repair is associated with less chronic pain, and foreign body sensation compared with heavyweight mesh without any difference in recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
30
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 41 publications
3
30
0
4
Order By: Relevance
“…In open groin hernia surgery, several meta-analyses of randomised trials have now shown that lightweight (flat) meshes do not have an advantage in the short-term, but are associated with less chronic (C6 months) pain and foreign body feeling [18,19], although the incidence of severe chronic groin pain is not decreased [20]. Importantly, this does not increase the recurrence rate at one year (range 6-60 months), although caution is still needed in large (direct) hernias with a potential increased risk for mesh migration into the defect, especially when some specific points for mesh fixation are not taken into account [21][22][23].…”
Section: Materials Reduced (Or Lightweight Large Pore) Meshesmentioning
confidence: 99%
“…In open groin hernia surgery, several meta-analyses of randomised trials have now shown that lightweight (flat) meshes do not have an advantage in the short-term, but are associated with less chronic (C6 months) pain and foreign body feeling [18,19], although the incidence of severe chronic groin pain is not decreased [20]. Importantly, this does not increase the recurrence rate at one year (range 6-60 months), although caution is still needed in large (direct) hernias with a potential increased risk for mesh migration into the defect, especially when some specific points for mesh fixation are not taken into account [21][22][23].…”
Section: Materials Reduced (Or Lightweight Large Pore) Meshesmentioning
confidence: 99%
“…At present, tension-free preshaped mesh hernioplasties have become a gold standard for most operating surgeons and over the last decade several types of meshes have evolved, and are used as single flat meshes or used in conjunction with three dimensional plugs. [9][10][11] In 1984, Lichtenstein addressed the issue of tension by popularizing routine use of mesh (monofilament polypropyelene meshes) which was laid on posterior wall of the inguinal canal, and a slit made at the lateral end of the mesh, creating two tails, which pass around the cord as it emerges from the internal ring. Presently newer mesh concepts are the current interest which has less chronic pain, earlier return to normal activities without compromising on recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have compared heavyweight with lightweight meshes in open anterior hernia repair and revealed a significant reduction in foreign body feeling and overall post-operative pain [11][12][13][14]. Lightweight meshes are, therefore, recommended as the material of choice in primary open inguinal hernioplasty [15].…”
mentioning
confidence: 99%